Hyper-Reflecting Foci in Multiple Sclerosis Retina Associate With Macrophage/Microglia-Derived Cytokines in Cerebrospinal Fluid - Puthenparampil, Marco; Torresin, Tommaso; Franciotta, Silvia; Marin, Annachiara; De Napoli, Federica; Mauceri, Valentina Annamaria; Miante, Silvia; Pilotto, Elisabetta; Midena, Edoardo; Gallo, Paolo (Frontiers in Immunology, 2022)
Background. Increasing evidence suggests that retinal hyper-reflecting foci (HRF) might be clusters of activated and proliferating microglia. Since microglia is widespread activated in multiple sclerosis (MS) brain, its evaluation in retina may help to understand and monitor MS-related pathology. Aim. To investigate the association of HRF with cerebrospinal fluid (CSF) cytokines and MRI parameters in Relapsing-Remitting MS (RRMS). Methods. Nineteen RRMS at clinical onset and 15 non-inflammatory neurological disorders (NIND) underwent brain 3T MRI and CSF examination. Optical Coherence Tomography (OCT) analysis, including HRF count, was performed on RRMS patients. Sixty-nine cytokines/chemokines were analyzed in the CSF by Multiplex technology. Results. In RRMS, HRF count in Ganglion Cell Layer (GCL) associated with IL-1Ra, IL-9, IL-15, IFN-, and G-CSF. Moreover, in RRMS patients CSF concentrations of IL-1Ra and G-CSF associated with global cortical thickness. HRF count in Inner Nuclear Layer (INL) correlated with IL-22, IL-34, IL-35, CXCL-2, CXCL-10, and CXCL-13, and multivariate analysis confirmed a strong association (r2: 0.47) with both CXCL-2 (: -0.965, p=0.0052) and CXCL-13 (: 0.241, p=0.018). This latter cytokine increased in RRMS with high HRF count compared with NIND and RRMS with low HRF count. Finally, CXCL-13/CXCL-2 ratio strongly associated with HRF count (r: 0.8, p<0.005) and cortical lesions volume (r: 0.5, p<0.05). Conclusions. The association of HRF with intrathecally produced monocyte/microglia-derived cytokines confirms their microglial origin and indicates they are worth of further evaluation as markers of activated microglia.